Salmonella Typhimurium commercial vaccine protects chickens against S. Infantis challenge - Joaquim, Patricia Estefania (2025)
Background: As an outcome of the implementation of monitoring and control programs in the poultry industry, including vaccination, there is a declining trend in the prevalence of Salmonella Enteritidis and S. Typhimurium. Consequently, a variety of other Salmonella serotypes also associated with human infections, such as S. Infantis, have emerged worldwide. In this work, we explored the protection conferred by a live attenuated S. Typhimurium vaccine against S. Infantis.